2019
DOI: 10.1093/ehjci/jez258
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of [15O]H2O positron emission tomography-derived global and regional myocardial perfusion

Abstract: Aims To evaluate the prognostic value of global and regional quantitative [15O]H2O positron emission tomography (PET) perfusion. Methods and results In this retrospective study, 648 patients with suspected or known coronary artery disease (CAD) who underwent [15O]H2O PET were followed for the occurrence of death and myocardial infarction (MI). Global and regional hyperaemic myocardial blood flow (hMBF) and coronary flow reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 21 publications
5
45
0
Order By: Relevance
“…The role of MBF and MFR (global or regional) in CAD prognostication was beyond the scope of the present study. However, to the extent that it has demonstrated stress MBF to be a more robust predictor of CAD than MFR particularly at the 50% stenosis level, the results are consistent with outcome data of at least 2 prior studies 6,21 and suggest reasons (e.g., technical, methodological, and population selection) for potential outcome differences with others, which found MFR superior. 7,8,22 The reader should keep in mind in the setting of CAD, outcomes (e.g., CV death or MI) in the vast majority of patients ultimately are indicative of MBF inadequate to meet a given level of myocardial oxygen demand (i.e., ischemia/infarction).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The role of MBF and MFR (global or regional) in CAD prognostication was beyond the scope of the present study. However, to the extent that it has demonstrated stress MBF to be a more robust predictor of CAD than MFR particularly at the 50% stenosis level, the results are consistent with outcome data of at least 2 prior studies 6,21 and suggest reasons (e.g., technical, methodological, and population selection) for potential outcome differences with others, which found MFR superior. 7,8,22 The reader should keep in mind in the setting of CAD, outcomes (e.g., CV death or MI) in the vast majority of patients ultimately are indicative of MBF inadequate to meet a given level of myocardial oxygen demand (i.e., ischemia/infarction).…”
Section: Discussionsupporting
confidence: 82%
“…Unsurprisingly, greater in the human study (± 1.14 mL/min/g) 25 vs the porcine (± 0.75 mL/min/g). 26 Thus, as with the present investigation and others, 12,21 it is becoming increasing clear it is the physiological parameter which matters most. It is very unlikely a level of stress requiring MBF 3.0 mL/min/g (think * 10 to 15 METs 27 ) will be met, without ischemia, by maximal MBF \ 2 mL/min/g ( Figure 8B) simply because rest MBF is 0.50 with stress MBF 1.50 and MFR = 3.0.…”
Section: Important Conceptual Issue (Briefly Alluded To In the Text)supporting
confidence: 66%
See 1 more Smart Citation
“…Studies have shown that global MFR provides prognostic information that is independent of the presence of regional myocardial ischemia [15,16,20]. In these studies using [29]. The investigators found that both global and regional sMBF had similar prognostic value in predicting the composite of death and MI, while the combination of global and regional sMBF did not improve the prognostic performance compared to either alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although CFR has been shown to be of incremental prognostic value it seems justified that for diagnostic purposes stress-only PET protocols suffice, obviating the need for baseline perfusion imaging leading to a reduction of radiation dose and scan acquisition time [21,22]. Furthermore, as recently published, [ 15 O]H2O PET derived hyperaemic MBF predicts adverse patient outcome independently of CFR in patients with suspected CAD [23].…”
Section: [ 15 O]h 2 O Pet Perfusion Imagingmentioning
confidence: 99%